Intervention of lavender aromatherapy and acupressure to reduce pain scale in postoperative sectio caesarea patients - Anggoro Sugito; Ta’adi Ta’adi; Djamalludin Ramlan; Rr. Sri Endang Pujiastuti (Universitas Muhammadiyah Semarang, 2023)
Sectio Caesarea surgery causes pain on a mild to severe scale in patients, impacting hemodynamic conditions, so attention is needed to this problem and its management with non-pharmacological therapy using aromatherapy and acupressure as a treatment companion in health services. The aim of the study was to analyze the effect of lavender aromatherapy and acupressure interventions on reducing the pain scale in postoperative sectio caesarea patients. This study used a quasi-experimental design with a pre-test and post-test with a control group design with a total sample of 16 respondents in each group taken by random sampling system. The group was given lavender aromatherapy intervention and acupressure, while the control group was only given lavender aromatherapy. The results of the research from the t-test showed that the administration of aromatherapy and acupressure had an effect on reducing the pain scale of postoperative sectio caesarea patients with a p-value = 0.000 and a decrease in the mean pain scale from 4.44 (pre-test) to 2.50 (post-test). This shows that aromatherapy and acupressure as complementary therapies can be used as non-pharmacological therapies as supporting treatment and alternative self-care to assist in overcoming pain problems in postoperative sectio caesarea patients. This study shows that lavender aromatherapy and acupressure effectively reduce pain scales in postoperative sectio caesarea patients.